1988
DOI: 10.1097/00000658-198807000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cancer of the Liver

Abstract: The factors influencing survival for patients with cancer of the liver were studied by reviewing the records of 414 patients operated on in a private oncology practice. Approximately half (47%) had colorectal metastasis; 17% had metastatic breast carcinoma, 14% had malignant hepatoma, 5% had metastatic melanoma, and the remainder had a variety of primary cancers. Eighty-two per cent of all patients had advanced liver disease when first diagnosed. One quarter of the patients had some type of resection; the rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Aigner and colleagues [11] reported early remission rates of 30%--80% after ILP with dacarbazine in patients with measurable disease, but recurrences in all of them within 4 months. If the concept that dacarbazine is inactive until it has passed through the liver is Correct, then one possibility is that some of the effects seen Were produced by hyperthermia during ILP [42][43][44]. Another Possibility is that significant levels of dacarbazine were achieved in the systemic circulation, either during the ILP as a result of leakage or afterwards by release of drug from the tissues of the limb following its revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Aigner and colleagues [11] reported early remission rates of 30%--80% after ILP with dacarbazine in patients with measurable disease, but recurrences in all of them within 4 months. If the concept that dacarbazine is inactive until it has passed through the liver is Correct, then one possibility is that some of the effects seen Were produced by hyperthermia during ILP [42][43][44]. Another Possibility is that significant levels of dacarbazine were achieved in the systemic circulation, either during the ILP as a result of leakage or afterwards by release of drug from the tissues of the limb following its revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…H&E stained mouse liver1 week post induction of metastases. Tumour cell aggregates (arrow) in the hepatic sinusoids (S) represent early signs of metastatic liver involvement.…”
mentioning
confidence: 99%
“…Five‐year survivals in reported series range from 23%7 to 40%,8 and there is evidence that only one‐fourth to one‐third of patients who have a hepatic metastasis may benefit from resective surgery. In this regard, to our knowledge, multivariate analysis has been reported in only five other papers,1,4, and all those studies found that radical surgery (in which there was an absence of residual manifestation of an intrahepatic and/or extrahepatic disease and negative resection margins) was one of the most important factors for a better prognosis. Other factors identified to be important for an improved prognosis were the stage of primary tumor,1,9 the stage of hepatic metastasis,10 the number of metastases,1,4 the size of the lesion (not more than 8 cm), and the disease‐free interval before the hepatic resection 1…”
Section: Discussionmentioning
confidence: 87%